Principles of Decoration in the Roman World. - Haug, Annette; Lauritsen, M. Taylor (Berlin/Boston : Walter de Gruyter GmbH, 2021)
DECOR is the first series that considers decorative phenomena in a comprehensive way. It moves away from the study of single decorative elements in isolation, focusing instead upon their spatial-architectural and visual integration. This serves as the starting point for a differentiated analysis of image- or decor-spaces. The geographical focus is on Italy, the chronological framework ranges from the 2ndcentury B.C. to the late 1st century A.D.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books